Contribution of Rural Cooperative Institutions to Sustainable Income Generation - Kharel, Tika Ram; Varghese, Manoj (The Management Review, 2026)
This study aims to find how the role of rural cooperatives in the implementation of Income Generating Activities (IGA) helps to improve the livelihood of people living in rural areas. While a number of cooperative programs and activities have been activated, their effectiveness in creating jobs within the neighborhood and local micro credits are still inadequately studied, and hence, there exists a lacuna in the already available body of knowledge. The overall aim of this study is to evaluate the role of the cooperatives in job creation and to evaluate the effect of micro credit on the IGAs in the study area. The survey method of descriptive research design was used and the data presented was obtained from both primary and secondary sources. The total households were 625 with simple random sampling technique of 120 households was taken. Information was gathered using a structured questionnaire with 25 closed-ended questions, participants were given help if needed. It was observed that agriculture is the main livelihood pursued by the members with 66.33% of the population engaged in agricultural pursuits and a satisfactory number of members, 20.67% involved in entrepreneurship and 13% participating in business. To improve economic empowerment and secure sustainable development, however, there is need for further strengthening of the delivery of credit, financial diversification, awareness creation and capital mobilisation/accessibility.